2017
DOI: 10.3389/fpsyg.2017.01657
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Brains and the Changing Rules of Neuroplasticity: Implications for Learning and Recovery

Abstract: A growing number of research publications have illustrated the remarkable ability of the brain to reorganize itself in response to various sensory experiences. A traditional view of this plastic nature of the brain is that it is predominantly limited to short epochs during early development. Although examples showing that neuroplasticity exists outside of these finite time-windows have existed for some time, it is only recently that we have started to develop a fuller understanding of the different regulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 139 publications
(153 reference statements)
0
93
0
3
Order By: Relevance
“…Structural changes in inhibitory neurons seen in LPZ suggest that dynamic changes in inhibitory tone may represent a global rule for initiation of plasticity and adjustment of cortical activity following peripheral injury in adults (Keck et al, 2011;Resnik and Polley, 2017), but it is unclear if this plasticity can be modulated by top-down pathways. Identifying precise cellular mechanisms of plasticity after injury, as well as defining potential roles of attention in this process may prove to be crucial for development of novel translational approaches for treatment of brain injury (Voss et al, 2017).…”
Section: Plasticity In the Adult Cortexmentioning
confidence: 99%
“…Structural changes in inhibitory neurons seen in LPZ suggest that dynamic changes in inhibitory tone may represent a global rule for initiation of plasticity and adjustment of cortical activity following peripheral injury in adults (Keck et al, 2011;Resnik and Polley, 2017), but it is unclear if this plasticity can be modulated by top-down pathways. Identifying precise cellular mechanisms of plasticity after injury, as well as defining potential roles of attention in this process may prove to be crucial for development of novel translational approaches for treatment of brain injury (Voss et al, 2017).…”
Section: Plasticity In the Adult Cortexmentioning
confidence: 99%
“…While the brain may be able to adapt to perimenopausal changes in estrogen receptor networks [166], these processes may also give rise to neurological symptoms, such as cognitive dysfunction [37], particularly in women with lower capacity for neuroplastic adaptation [167].…”
Section: Neural Adaptationsmentioning
confidence: 99%
“…E2 is a potent regulator of neuroplasticity in the female brain [59], and it has been suggested that neuroplasticity may play a vital part in understanding the borders between normal aging and early stages of AD [231]. Several of the neural symptoms observed in AD are also found in normal brain aging, including accumulation of amyloid protein and brain atrophy [231,232,233,234], and the levels of neuropathology that can be tolerated without neurological symptoms and cognitive decline varies substantially between individuals [167]. Interestingly, research indicates that intensity and duration of perimenopausal symptoms may represent warning signs for an increased risk of adverse health consequences later in life, particularly neurodegenerative diseases such as AD [37].…”
Section: Potential Links Between Pregnancy Menopause and Brain Agingmentioning
confidence: 99%
“…A well‐known feature of cortical plasticity is that it is primarily constrained within limited time epochs during early development (Hensch, ; Knudsen, )—although the cortex does retain some plasticity throughout the lifespan (de Villers‐Sidani et al, ; Mishra, de Villers‐Sidani, Merzenich, & Gazzaley, ; Voss, Thomas, Cisneros‐Franco, & de Villers‐Sidani, ). The same is true for visual deprivation, where the loss of sight early in life typically results in significantly more robust cross‐modal plastic changes than for adult‐onset loss of sight (Büchel et al, ; Burton, Snyder, Conturo, et al, ; Burton, Snyder, Diamond, & Raichle, ; Sadato, Okada, Honda, & Yonekura, ; Voss, Gougoux, Lassonde, Zatorre, & Lepore, ; Voss, Gougoux, Zatorre, Lassonde, & Lepore, ).…”
Section: Critical and Sensitive Periods For Cross‐modal Plasticity Fomentioning
confidence: 99%